Learning From Home: A Study of the Role of Parents in Online Learning during the Covid-19 Pandemic in Junior High Schools - Malim Harahap (Program Pascasarjana UMSB, 2022)
This study was conducted to determine the role of parents in educating children learning from home, as well as the implementation and obstacles faced by parents in educating children to learn from home during the Covid-19 pandemic at SMP Muhammadiyah 1 Teluk Kuantan. This study was motivated by symptoms in the field such as obstacles felt by parents when carrying out a role in learning from home, the difficulty of the learning process carried out online, limited learning time and process, internet connection and other things. This study uses a qualitative descriptive approach, namely to determine the role of parents in educating children learning from home,as well as the implementation and obstacles faced by parents in educating children to learn from home during the Covid-19 pandemic at SMP Muhammadiyah 1 Teluk Kuantan. The result of the study is that the role of parents in educating children learning from home is realized quite well in the midst of various kinds of professions and busyness carried out by parents. The implementation of learning from home during the Covid-19 pandemic does not necessarily run smoothly, complaints that are often expressed by teachers such as the difficulty of the learning process carried out online, limited learning time and process, internet connection and other things. This is also so many obstacles faced by parents in educating children in learning from home during the Covid-19 pandemic, namely for parents who have high, medium and low busyness such as not being able to accompany children's activities, not understanding children's learning, not having gadgets and internet networks, and situations and conditions at home are not comfortable for children.